Increased Militarization in the Post-War Context: A Barrier to the Implementation of UN Security Council Resolution 1325 in Sri Lanka - Manogaran, V. (University of Jaffna, 2022)
War significantly contributes to numerous human rights violations and negatively impacts individuals’ lives. Even if the war is over, the post-war environment places additional demands on those impacted by the conflict and has a particularly profound effect on women’s lives. Therefore, the United Nations Security Council passed Resolution 1325 to protect women and involve them in peacebuilding activities. Nonetheless, many nations struggle to implement UNSCR 1325 due to various factors, including militarization. With respect to UNSCR 1325, this paper aims to examine how increased militarization in post-conflict contexts creates barriers to its implementation by looking at the Sri Lankan context, specifically the northern and eastern provinces of Sri Lanka. Also, this paper provides an overview of UNSCR 1325 and its implementation at the global level. The research methodology used in this research paper was qualitative, and desk research was used as the data collection method. This paper demonstrates that military land occupation hinders the return of women IDPs to their native lands, thereby impacting their lives. In the case of partial land release, security forces impose restrictions on returning women. In addition, the presence of the military increases the risk of sexual exploitation of women by military personnel. This situation creates insecurity for war affected women, especially widows and women who head their households. Moreover, this threat, reliance on the military for permission, and insecurity prevent women from engaging in economic activities, thereby rendering them economically vulnerable. In addition, because of these fears and threats, war-affected Tamil women are reluctant to participate in the peacebuilding and reconstruction process. Consequently, the increased militarization in the war-torn northern and eastern provinces poses a significant obstacle to the implementation and success of the WPS agenda outlined in UNSCR 1325. Therefore, this paper recommends that in designing and implementing their National Action Plan and other national-level strategies, the State should consider the impediment posed by the rising militarization and should take action to curtail the unessential increased militarization in the northern and eastern provinces of Sri Lanka.
Keywords: Militarization; Post-war; Sri Lanka; UNSCR 1325; Women